Comparative Performance of Islamic Banks in Indonesia and Malaysia Using Islamic Performance Index and Financial Ratios - Fadila, Ega Friska; Wahyudi, Muhammad; Khotijah, Siti Afidatul (Institut Bisnis dan Informatika Kesatuan, 2025)
Islamic banking operates according to Islamic principles and is oriented towards profitability, social justice, and public welfare, in contrast to conventional banks. This study aims to compare the performance of Islamic banking in Indonesia and Malaysia using the Islamic Performance Index (IPI) and conventional financial indicators such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). Islamic banking, which operates based on Islamic sharia principles, has broader objectives, namely social justice and public welfare. The methodology used is a systematic review following the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) protocol, involving articles published between 2020 and 2024 from various academic sources. Out of the 604 articles reviewed, 10 met the study criteria. The study results indicate significant differences in the performance of Islamic banks in the two countries, influenced by factors such as asset size, regulations, management strategies, and economic environments. These findings provide valuable insights for stakeholders in developing more optimal Islamic banking policies and strategies while contributing to community welfare. This research is expected to serve as a reference for policymakers and researchers in the future.